Manufacturing method of needle-shaped prefabricated body for compounding cast iron matrix
By selecting suitable materials and processes, high-strength needle-shaped preforms are prepared, which solves the problems of complex preparation methods, high cost and unstable quality in the prior art, and achieves the performance improvement of cast iron matrix composite materials.
Patent Information
- Application Number
- CN202411731909.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-14
AI Technical Summary
The existing prefabricated needle-shaped body preparation methods have problems such as complex processing, high cost, and unstable quality, which are difficult to meet the needs of large-scale applications.
By selecting high-strength metal powder as the base material, ceramic particle powder as the reinforcement phase, and adding auxiliary agents, needle-shaped preforms are prepared by spray drying, ball milling, mold extrusion molding, heat treatment and electroplating.
It realizes efficient and stable preparation of needle-shaped preforms, improves the mechanical properties, wear resistance and interface combination performance of cast iron matrix composite materials, and is suitable for high-load and wear-resistant environments.
Abstract
Description
Technical Field
[0001] The invention belongs to the preparation technology of cast iron matrix composite materials, and particularly relates to a method for manufacturing a needle-shaped preform used for cast iron matrix composites. Background Art
[0002] As a common engineering material, cast iron has good casting properties and high wear resistance and is widely used in the automotive, machinery, chemical and other fields. In recent years, in order to improve the mechanical properties of cast iron and its durability under extreme conditions, researchers have tried to composite other high-performance materials with the cast iron matrix. However, traditional composite materials usually rely on particles or short fibers as reinforcement phases, and the distribution, forming and interface bonding of these reinforcement phases remain one of the key bottlenecks in the performance of composite materials.
[0003] As a new type of reinforcement material, the needle-shaped preform is an ideal reinforcement material due to its long strip shape, excellent tensile strength and good directional distribution characteristics. The needle-shaped preform can improve the strength, toughness and wear resistance of composite materials, but the existing preparation method of the needle-shaped preform has problems such as complex processing, high cost and unstable quality, and cannot meet the needs of large-scale applications.
[0004] Therefore, it is of great practical significance to develop a manufacturing method that is efficient, low-cost and capable of stably preparing needle-shaped preforms. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention aims to provide a method for manufacturing a needle-shaped preform for cast iron matrix composite, so as to solve the problems raised in the above background technology.
[0006] The present invention is achieved through the following technical scheme: a method for manufacturing a needle-shaped preform for cast iron matrix composite, comprising the following steps: selecting high-strength metal powder as a base material, selecting ceramic particle powder as a reinforcing phase, and adding an auxiliary agent to prepare the needle-shaped preform.
[0007] As a preferred embodiment, the ratio of the base material to the reinforcement phase is 50-70wt% and 30-50wt%, specifically:
[0008] Basic materials: chromium powder, molybdenum powder, nickel powder;
[0009] Reinforcement phase: silicon carbide SiC, boron nitride BN;
[0010] Auxiliary agents: polyvinyl alcohol (PVA), phosphate ester.
[0011] As a preferred embodiment, the specific steps of selecting high-strength metal powder as the base material, selecting ceramic particle powder as the reinforcement phase, and adding auxiliary agents to prepare the needle-shaped preform are as follows:
[0012] Step 1, Powder pretreatment
[0013] The base material is spray dried to prepare spherical powder, and the particle size is controlled between 10-20 μm; the reinforcing phase is treated by acid washing to remove surface impurities, and then plasma surface modification is performed to enhance the interfacial activity;
[0014] Step 2, powder mixing
[0015] Add the base material and reinforcing phase, add appropriate amount of polyvinyl alcohol (PVA) and phosphate ester in a ball mill, and mix at 600 rpm for 2 hours until the powder is evenly dispersed without agglomeration;
[0016] Step 3, needle forming
[0017] The mixed powder is extruded into a needle-shaped body with a diameter of 1-5 mm and a length of 10-20 mm through a fine-pore die by using die extrusion molding technology; after molding, a preliminary drying treatment is performed;
[0018] Step 4: Heat treatment
[0019] The needle-shaped preform is placed in a high-temperature sintering furnace, with argon as the protective atmosphere, the sintering temperature is 800-1200°C, and the sintering time is 2-4 hours; this is used to improve the mechanical strength and thermal stability of the needle-shaped preform;
[0020] Step 5, surface modification
[0021] The sintered needle-shaped preform is electroplated to enhance the interface bonding performance between the surface of the preform and the cast iron matrix.
[0022] As a preferred embodiment, in step 5, the specific steps of the electroplating process are:
[0023] Step 5.1, raw materials and solution preparation:
[0024] A nickel sulfate solution is used as the plating solution, wherein: the nickel ion concentration is 200-300g / L, sodium chloride and boric acid are used as plating aids to adjust the current density and the quality of the coating; and the pH value of the plating solution is between 4.0 and 4.5.
[0025] Step 5.2, Plating tank configuration:
[0026] When nickel is plated, the cathode is a needle-shaped body and the anode is a nickel plate, which is used for uniform deposition of the coating;
[0027] Step 5.3, pretreatment: clean the needle-shaped body to remove surface oil and oxides; hang the cleaned needle-shaped body in the electroplating tank, connect it as a cathode, apply a constant current, and the electroplating time is 30-60 minutes;
[0028] Step 5.4, post-treatment: After the coating deposition is completed, the needle-shaped body is taken out, washed and dried or pickled to remove the surface plating solution residue, ensuring that the coating is smooth and the nickel plating layer thickness is between 5-25μm to ensure good corrosion resistance, wear resistance and bonding with the cast iron substrate.
[0029] As a preferred embodiment, after the needle-shaped preform is prepared, the prepared needle-shaped preform is mixed with a cast iron matrix, and the needle-shaped preform is embedded into the cast iron matrix through a sand casting process to form a composite material. Specifically, during the cast iron pouring process, the needle-shaped preform is evenly added, the pouring temperature is controlled at 1350-1450°C, and a stirring device is used to ensure that the preform is evenly distributed in the matrix.
[0030] After adopting the above technical scheme, the beneficial effects of the present invention are: by reasonably selecting raw materials, optimizing the molding process, and accurately controlling the heat treatment and surface modification process, a preform with a needle-like structure can be efficiently and stably prepared, thereby manufacturing a high-performance cast iron matrix composite material. Compared with traditional composite materials, the present invention has the following advantages: High-performance enhancement: The needle-like preform can form excellent mechanical properties in the cast iron matrix, improve the strength, hardness and wear resistance of the cast iron material, and is particularly suitable for high-load and wear-resistant working environments. Optimized interface bonding: The surface modification treatment improves the bonding strength between the needle-like preform and the cast iron matrix, avoiding the problem of poor interface bonding of traditional particle reinforcement materials. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] The present invention provides a technical solution: a method for manufacturing a needle-shaped preform for cast iron matrix composite, comprising the following steps: selecting high-strength metal powder as a base material, selecting ceramic particle powder as a reinforcing phase, and adding an auxiliary agent to prepare the needle-shaped preform.
[0033] The ratio of the base material to the reinforcement phase is 50-70wt% and 30-50wt%, specifically:
[0034] Basic materials: chromium powder, molybdenum powder, nickel powder;
[0035] Reinforcement phase: silicon carbide SiC, boron nitride BN;
[0036] Auxiliary agents: polyvinyl alcohol (PVA), phosphate ester.
[0037] The specific steps of selecting high-strength metal powder as the base material, selecting ceramic particle powder as the reinforcement phase, and adding auxiliary agents to prepare the needle-shaped preform are as follows:
[0038] Step 1, Powder pretreatment
[0039] The base material is spray dried to prepare spherical powder, and the particle size is controlled between 10-20 μm; the reinforcing phase is treated by acid washing to remove surface impurities, and then plasma surface modification is performed to enhance the interfacial activity;
[0040] Step 2, powder mixing
[0041] Add the base material and reinforcing phase, add appropriate amount of polyvinyl alcohol (PVA) and phosphate ester in a ball mill, and mix at 600 rpm for 2 hours until the powder is evenly dispersed without agglomeration;
[0042] Step 3, needle forming
[0043] The mixed powder is extruded into a needle-shaped body with a diameter of 1-5 mm and a length of 10-20 mm through a fine-pore die by using die extrusion molding technology; after molding, a preliminary drying treatment is performed;
[0044] Step 4: Heat treatment
[0045] The needle-shaped preform is placed in a high-temperature sintering furnace, with argon as the protective atmosphere, the sintering temperature is 800-1200°C, and the sintering time is 2-4 hours; this is used to improve the mechanical strength and thermal stability of the needle-shaped preform;
[0046] Step 5, surface modification
[0047] The sintered needle-shaped preform is electroplated to enhance the interface bonding performance between the surface of the preform and the cast iron matrix.
[0048] In step 5, the specific steps of the electroplating process are:
[0049] Step 5.1, raw materials and solution preparation:
[0050] A nickel sulfate solution is used as the plating solution, wherein: the nickel ion concentration is 200-300g / L, sodium chloride and boric acid are used as plating aids to adjust the current density and the quality of the coating; and the pH value of the plating solution is between 4.0 and 4.5.
[0051] Step 5.2, Plating tank configuration:
[0052] When nickel is plated, the cathode is a needle-shaped body and the anode is a nickel plate, which is used for uniform deposition of the coating;
[0053] Step 5.3, pretreatment: clean the needle-shaped body to remove surface oil and oxides; hang the cleaned needle-shaped body in the electroplating tank, connect it as a cathode, apply a constant current, and the electroplating time is 30-60 minutes;
[0054] Step 5.4, post-treatment: After the coating deposition is completed, the needle-shaped body is taken out, washed and dried or pickled to remove the surface plating solution residue, ensuring that the coating is smooth and the nickel plating layer thickness is between 5-25μm to ensure good corrosion resistance, wear resistance and bonding with the cast iron substrate.
[0055] After the needle-shaped preform is prepared, the prepared needle-shaped preform is mixed with a cast iron matrix, and the needle-shaped preform is embedded in the cast iron matrix through a sand casting process to form a composite material. Specifically, during the cast iron pouring process, the needle-shaped preform is evenly added, the pouring temperature is controlled at 1350-1450°C, and a stirring device is used to ensure that the preform is evenly distributed in the matrix.
[0056] As an embodiment of the present invention: molybdenum powder and silicon carbide powder are selected as the base materials, wherein chromium powder (60wt%), SiC particles (38wt%), and auxiliary agent (2wt%) are used. The directional deposition method is adopted, and the directional deposition is formed into a needle-like structure through spraying and heating technology. The formed needle-like preform is subjected to temperature-controlled sintering, the temperature is maintained at 800°C, and the sintering time is 2 hours, and finally a needle-like preform with high strength is formed. After surface chemical plating treatment, it is mixed with a cast iron matrix and a composite material is manufactured through a sand casting process.
[0057] The performance of the composite material was tested and compared with the products in the prior art, specifically:
[0058] 1. Mechanical properties testing
[0059] 1.1 Hardness test
[0060] Test standard: Brinell hardness (HB) test method is used according to ISO 6506 or ASTM E10 standard.
[0061] Test equipment: Brinell hardness tester, steel ball indenter diameter is 10mm, loading force is 3000kgf.
[0062] Test steps:
[0063] Take samples from the prepared composite material, prepare test blocks, and grind the surface until it is smooth and free of defects;
[0064] A constant load was applied to the sample surface and maintained for 15 seconds;
[0065] Read the indentation diameter and calculate the Brinell hardness value: Test each sample 5 times and take the average value.
[0066] 1.2 Tensile strength test
[0067] Test standard: Tensile test shall be carried out in accordance with GB / T 228 or ASTM E8.
[0068] Testing equipment: Universal material testing machine (electronic tensile machine), accuracy ±0.5%.
[0069] Test steps:
[0070] Prepare tensile specimens with standard dumbbell-shaped specifications (e.g., 12.5 mm wide and 50 mm gauge length);
[0071] Install the specimen in the testing machine fixture and apply tension until the specimen breaks;
[0072] According to the stress-strain curve, the tensile strength value (unit: MPa) was recorded.
[0073] Each sample was tested 3 times and the average value was taken.
[0074] 2. Wear resistance test
[0075] Test Standards
[0076] Wear resistance was evaluated by dry sand rubber wheel abrasion test according to ASTM G65.
[0077] Test equipment
[0078] Wear test machine, grinding wheel diameter 300mm, speed 200rpm;
[0079] The abrasive is standard quartz sand with a particle size range of 53-150μm.
[0080] Test steps
[0081] Sample preparation: The composite material was prepared into a rectangular specimen of 30×30×10 mm and polished to be flat;
[0082] Test conditions:
[0083] Loading force: 130N;
[0084] Abrasive flow rate: 300g / min;
[0085] Test time: 60 minutes;
[0086] Measurement method:
[0087] Weigh the sample before and after the test and calculate the wear rate: test each sample 3 times and take the average value.
[0088] 3. Corrosion resistance test
[0089] Test Standards
[0090] Corrosion resistance is evaluated by neutral salt spray testing according to ISO 9227.
[0091] Test equipment
[0092] Salt spray corrosion test chamber, spray temperature is controlled at 35℃;
[0093] The reagent is a 5wt% NaCl solution, and the pH value is adjusted to 6.5-7.2.
[0094] Test steps Sample preparation: Prepare composite material samples with a size of 50×50×5mm, clean and dry; Test conditions:
[0095] Salt spray time: 48 hours;
[0096] Spray rate: 1.5mL / h;
[0097] Evaluation method:
[0098] After the test, the samples were washed with distilled water and dried;
[0099] The mass change of the sample was measured by a precision balance and the corrosion weight loss was calculated (unit: g / m 2 );
[0100] Each sample was tested 3 times and the average value was taken.
[0101] 4. Thermal stability test
[0102] Test Standards
[0103] According to GB / T 4338 or ASTM E21 standards, the thermal stability of the material is evaluated through high temperature tensile test.
[0104] Test equipment
[0105] High temperature tensile testing machine, equipped with a high temperature furnace, with a temperature control accuracy of ±2°C.
[0106] Test steps Sample preparation: Prepare standard tensile specimens with the same specifications as the tensile strength test;
[0107] Test conditions:
[0108] The high temperature environment was set to 500°C and the stretching was performed after the temperature was kept constant for 30 minutes;
[0109] Record the tensile strength value at high temperature;
[0110] Calculate stability: Calculate strength retention by comparing high temperature tensile strength with room temperature tensile strength: Test each sample 3 times and take the average value.
[0111] The specific data is as follows:
[0112] Test items Prior art The present invention (Example 1) Improved results Hardness (HB) 260 320 +23% <![CDATA[Wear rate (mm 3 / Nm)]]> 0.22 0.15 -32% Tensile strength(MPa) 430 520 +21% <![CDATA[Corrosion resistance (g / m 2 )]]> 0.28 0.18 -35% Thermal stability (strength retention) 80% 95% +15%
[0113] Through clear testing methods and experimental data analysis, it is confirmed that the technical solution of the present invention has significant advantages over the existing technology in terms of mechanical properties, wear resistance, corrosion resistance and thermal stability, further proving the innovation and industrial application value of the present invention.
[0114] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for manufacturing a needle-shaped preform for cast iron matrix composite, characterized in that: The following steps are involved: High-strength metal powder is selected as the basic material, ceramic particle powder is selected as the reinforcement phase, and auxiliary agents are added to prepare the needle-shaped preform.
2. The method for manufacturing a needle-shaped preform for cast iron matrix composite according to claim 1, characterized in that: The ratio of the base material to the reinforcement phase is 50-70wt% and 30-50wt%, specifically: Basic materials: chromium powder, molybdenum powder, nickel powder; Reinforcement phase: silicon carbide SiC, boron nitride BN; Auxiliary agents: polyvinyl alcohol (PVA), phosphate ester.
3. The method for manufacturing a needle-shaped preform for cast iron matrix composite according to claim 2, characterized in that: The specific steps of selecting high-strength metal powder as the base material, selecting ceramic particle powder as the reinforcement phase, and adding auxiliary agents to prepare the needle-shaped preform are as follows: Step 1, Powder pretreatment The base material is spray dried to prepare spherical powder, and the particle size is controlled between 10-20 μm; the reinforcing phase is treated by acid washing to remove surface impurities, and then plasma surface modification is performed to enhance the interfacial activity; Step 2, powder mixing Add the base material and reinforcing phase, add appropriate amount of polyvinyl alcohol (PVA) and phosphate ester in a ball mill, and mix at 600 rpm for 2 hours until the powder is evenly dispersed without agglomeration; Step 3, needle forming The mixed powder is extruded into a needle-shaped body with a diameter of 1-5 mm and a length of 10-20 mm through a fine-pore die by using die extrusion molding technology; after molding, a preliminary drying treatment is performed; Step 4: Heat treatment The needle-shaped preform is placed in a high-temperature sintering furnace with argon as the protective atmosphere, the sintering temperature is 800-1200°C, and the sintering time is 2-4 hours; Used to improve the mechanical strength and thermal stability of the needle-shaped preform; Step 5, surface modification The sintered needle-shaped preform is electroplated to enhance the interface bonding performance between the surface of the preform and the cast iron matrix.
4. The method for manufacturing a needle-shaped preform for cast iron matrix composite according to claim 3, characterized in that: In step 5, the specific steps of the electroplating process are: Step 5.1, raw materials and solution preparation: A nickel sulfate solution is used as the plating solution, wherein: the nickel ion concentration is 200-300g / L, sodium chloride and boric acid are used as plating aids to adjust the current density and the quality of the coating; and the pH value of the plating solution is between 4.0 and 4.
5. Step 5.2, Plating tank configuration: When nickel is plated, the cathode is a needle-shaped body and the anode is a nickel plate, which is used for uniform deposition of the coating; Step 5.3, pretreatment: clean the needle-shaped body to remove surface oil and oxides; hang the cleaned needle-shaped body in the electroplating tank, connect it as a cathode, apply a constant current, and the electroplating time is 30-60 minutes; Step 5.4, post-treatment: After the coating deposition is completed, the needle-shaped body is taken out, washed and dried or pickled to remove the surface plating solution residue, ensuring that the coating is smooth and the nickel plating layer thickness is between 5-25μm to ensure good corrosion resistance, wear resistance and bonding with the cast iron substrate.
5. The method for manufacturing a needle-shaped preform for cast iron matrix composite according to claim 1, characterized in that: After the needle-shaped preform is prepared, the prepared needle-shaped preform is mixed with a cast iron matrix, and the needle-shaped preform is embedded in the cast iron matrix through a sand casting process to form a composite material. Specifically, during the cast iron pouring process, the needle-shaped preform is evenly added, the pouring temperature is controlled at 1350-1450°C, and a stirring device is used to ensure that the preform is evenly distributed in the matrix.